Context-Dependent Preferences and Innovation Strategy - Chen, Yuxin; Turut, Özge (Management Science, 2013)
Disruptive innovations introduce a new performance dimension into a product category, but often suffer from inferior performance on key performance dimensions of their existing substitutes. Hence, the followers of these innovations face an important decision to make: they must choose to improve the new technology either on the key performance dimension shared with the old technology or on the new performance dimension. This paper investigates which path firms should choose when they face such a dilemma in the absence of any cost or capability issues. In doing so, we integrate customer response into the theory of technological evolution and allow preferences on the product choices to be context dependent. We show that context-dependent preferences may encourage the follower to improve the new technology on the new performance dimension. Later, we extend our game to a dynamic one and show that the context-dependent preferences may cause the pioneer to innovate less. This paper was accepted by J. Miguel Villas-Boas, marketing.